1987
DOI: 10.1007/bf02370640
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of inhibitory pseudomonads in the Pacific Northwest

Abstract: Incidence of pseudomonads inhibitory to the root growth of till and no-till seeded crops winter wheat (Triticum aestivum L.), pea ( Pisum sativum), lentil (Lens culinaris), and no-till winter barley (Hordeum vulgare), top and bottom of a seeded slope, and on the weed downy brome (Bromus tectorum) was investigated. Pseudomonads on the rhizoplane of these plants ranged from 10 6 to l0 8 colony-forming units (cfu) per gram dry weight of root. Neither tillage management nor site on a seeded slope affected colonizi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 15 publications
1
27
0
Order By: Relevance
“…Various investigations of the microflora associated with plant roots have provided evidence for a general occurrence of non-parasitic bacteria with a potential to inhibit or reduce plant growth (Campbell et al, 1986;Cherrington and Elliott, 1987;Elliott and Lynch, 1985;Gerhardson et al, 1985;Suslow and Schroth, 1982). These bacteria are assumed to induce detrimental effects in plants through the production of substances that affect root cell permeability or in other ways interfere with root physiological processes (Schippers et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Various investigations of the microflora associated with plant roots have provided evidence for a general occurrence of non-parasitic bacteria with a potential to inhibit or reduce plant growth (Campbell et al, 1986;Cherrington and Elliott, 1987;Elliott and Lynch, 1985;Gerhardson et al, 1985;Suslow and Schroth, 1982). These bacteria are assumed to induce detrimental effects in plants through the production of substances that affect root cell permeability or in other ways interfere with root physiological processes (Schippers et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Many of these DRB and their secondary metabolites are host-specific and the amount of root reduction was found to be concentration-dependent (Boyetchko and Holmstrom-Ruddick, 1995}. Other researchers have also indicated that the effect of rhizobacteria can be hostspecific (Cherrington and Elliott, 1987;Elliott and Lynch, 1985;Kennedy et al, 1991). Host-range tests on non-target hosts (Le., spring and Winter cereal crops) showed little or no detrimental effects to root and shoot growth, with some degree of plant growth promotion occurring in some cases, depending on the crop cultivar and rhizobacterial isolate (Boyetchko and Holmstrom-Ruddick, 1995).…”
Section: Deleterious Rhizobacteriamentioning
confidence: 95%
“…DRB have also been isolated from several weeds (Cherrington and Elliott 1987;Kremer and Kennedy 1996) including downy brome (Bromus tectorum) occurring in winter wheat fields (Kennedy et al 1991) and broadleaf weed seedlings (Kremer et al 1990;Souissi and Kremer 1994). Several investigators have reported the effectiveness of DRB as biocontrol agents against weeds (Kennedy et al 1991;Kennedy and Stubbs 2007;Kremer 1987).…”
Section: Introductionmentioning
confidence: 96%
“…Although the specific effects of DRB on weed plant growth usually resulted in reduced seed germination, growth inhibition, reduced root elongation and root deformation (Kremer and Kennedy 1996;Li and Kremer 2006), the impact of DRB on root architecture of weeds is still poorly understood. Since DRB are mostly plantspecific (Cherrington and Elliott 1987;Kennedy et al 1991;Suslow and Schroth 1982), detrimental effects on non-target plants are not expected to occur.…”
Section: Introductionmentioning
confidence: 97%